THE TWINS’ SITUATION IMPACT ON THE PERSONALITY DEVELOPMENT - Dumbrauska, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Since the moment of their birth between the twins develop a relationship that differs from the brother and sister relationships. Two children of the same age, growing under the same conditions, promote and develop their personalities. The twins' connections are so close that at a short time separation from each other, the twins suffer the same as been separated from their mother. The aim of the research: to research the twins' situation impact on the child's personality development. The research involves the analysis of the scientific pedagogical and psychological literature, structured interviews are used in the empirical research. The obtained data from the parents interviews of 37 twins' pairs have been analyzed. Results: the role distribution, the twins bilateral/reciprocal competitiveness, speech-therapist's necessity, self-contentedness inside the pair, communication with other children, amount of vocabulary at an early age are clarified in the twins pair, presence of cryptophasia, emphasizing of similarity, difference, difficulty to formulate thoughts and emotions by words. Conclusions: twins' situations impact essentially differs, depending on the type of twins: MZ, DZ or different gender. Their bilateral/reciprocal interrelation indexes are different: the role distribution in the pair, desire to competitiveness, be closely self-contained inside their pair and disallow to let others into their dyad or to be open to communication with other people.